(untitled) (Journal of the College of Basic Education, 2023)
The two researchers realized, through their field work in teaching, thatThere is a problem that students of the Department of Islamic Education often suffer from in the curricula of educational subjects.prescribed for all academic levels, as many of its principles and contents are matters thatIt is difficult for students to understand and comprehend them properly, so these subjects are difficult compared towith the rest of the other subjects, related to their specialization, in addition to that they put memorization and indoctrinationinformation in the first place instead of being interested in patterns of thinking and comprehension, and believesThe two researchers said that the main reason may be due to the presentation of the scientific material below the required level.It is devoid in its contents, vocabulary, methods and means of suspense and excitement.And the lack of connection with the needs of students and their problems.Based on the above, the two researchers thought about conducting the current study, perhaps contributing to addressingproblem or mitigate it.